THE ROLE OF RESOURCES IN THE TRAINING PROGRAM TO IMPROVE EFFICIENCY AND EFFECTIVENESS - Wahira; Abd Hamid (Media Inovasi Pendidikan dan Publikasi, 2024)
Resources have a very important role in training programs to improve their efficiency and effectiveness. The purpose of this study is (1) to describe the use of resources in the training program to improve efficiency and effectiveness (2) to explain the impact of lack of human resources in the training program. This research was compiled and described using qualitative methods with literature review techniques. Meanwhile, the data analysis was carried out in a qualitative descriptive manner which was carried out after collecting literature data. The results showed that (1) using resources well, training programs can run more efficiently, produce better results, and provide greater added value for participants and organizing organizations; (2) lack of human resources can hinder the achievement of the objectives of the training program and reduce the value obtained by participants. Therefore, it is important to ensure that the training program has sufficient and competent manpower to support effective and quality operations. By utilizing the resources in the training program optimally, the training program can achieve efficiency in the use of time and budget, as well as effectiveness in achieving the learning objectives set